PENDAPATAN DAN KESEJAHTERAAN RUMAH TANGGA NELAYAN OBOR DI KOTA BANDAR LAMPUNG - Fadilah F; Zainal Abidin; Umi Kalsum (Lampung University, 2014)
This research aimed to analyze the income, consumption patterns of food and non-food, and (3) household welfare of torch fisherman in the City of Bandar Lampung. The number of samples was 43 people using cencus method. The method used was survey method by interviewing the samples using questionnaire. The data was extracted from the primary and secondary data. The results showed that the average income for a household was Rp30.187.572 per year. The household expenditures for food consumption were 60.09% of the household income, while the non-food consumption was 39,91%. Based on Sajogyo criteria (1997), 9,3% of the fisherman household were poor, 74,42% of them live moderately and the remaining 16,28% live well. Keywords: income, outcome, torch fisherman, welfare